Funciones narrativas e ideológicas de los personajes de inmigrantes y de sus descendientes en la narrativa española - Kołakowski, Marcin (Studia Romanica Posnaniensia, 2020)
The present paper is aimed to analyze how certain concepts of political identity are translated into poeticsof identity in contemporary Spanish narrative. The analysis covers four novels published since 1998,written by Spanish authors and which achieved high rates of sales and positive critical recognition. Thestudy was not limited to specific immigrant groups in order to reflect a variety of experiences and politicalpositions represented in the texts. The paper is a study of the image and functions of immigrantcharacters in selected Spanish novels of the last three decades: Háblame, musa, de aquel varón (1998) by Dulce Chacón, Ventajas de viajar en tren (2000) by Antonio Orejudo, Cosmofobia (2007) by Lucía Etxebarria and En la orilla (2013) by Rafael Chirbes. Sociologists and psychologists indicate three main classes of negative attitudes towards immigrants (citizen insecurity, threat to cultural identity and competitiveness in obtaining resources). Within this context the article aims to determine to what extent the literary representations of immigrant characters constitute reproductions or transgressions of culturally prefabricated images of the Other and explores the different narrative and ideological functions these characters play. The paper also studies the presence of discourses that support social exclusion of immigrants and the means of subverting them.